A MULTI-OBJECTIVE APPROACH TO PLANNING IN EMERGENCY LOGISTICS NETWORK DESIGN - Hong, Jae-Dong; Jeong, Ki-Young; Xie, Yuanchang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
This paper considers simultaneous strategic andoperational planning for the emergency logistics network (ELN) design. Emergency events make it so critical to distributeemergency supplies through emergency response facilities (ERFs) for rapidrecovery to the affected areas in a timely and efficient manner. But emergencycould prevent the ERF from providing the expected service, since the facilitycan be also damaged or destroyed by such an event. Thus, it is important to plana cost/distance-effective ELN, which is also reliable, less likely to bedisrupted at strategic level and robust, more likely to work well atoperational level. We adopt a multi-objective decision approach todesigning such an ELN. We present formulations for planning framework andoperating ELN to simultaneously determine the locations of ERF and to assignthe possible disaster area to ERF. A case study is conducted todemonstrate our models’ capability underthe risk of facility disruptions.